2014
DOI: 10.7166/25-2-685
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing as an Enabler for Enhanced Consumer Involvement

Abstract: This paper draws on previous work by the authors that aimed to use functional prototypes, produced using additive manufacturing (AM), as a means to draw customer input and preferences into the development of new products. This technique is referred to as Customer Interaction through Functional Prototypes (CIFP). The CIFP philosophy has been proven in both consumer and medical products. In recent years, the authors have developed further concepts of AM-enabled enhanced consumer involvement within their respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…This need is driven by the contrast between traditional subtractive manufacturing processes and AM. AM affords new modes of manufacture that are capable of geometries not possible using subtractive methods and batch sizes that allow customized parts to become economical [9,10], possibly enabling long-term visions such as mass-customization [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This need is driven by the contrast between traditional subtractive manufacturing processes and AM. AM affords new modes of manufacture that are capable of geometries not possible using subtractive methods and batch sizes that allow customized parts to become economical [9,10], possibly enabling long-term visions such as mass-customization [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Klahn et al [32] describe two strategies for using AM in design: a "manufacturing-driven design strategy" which uses AM for rapid prototyping and a "function-driven design strategy" which uses the unique advantages of AM for final production parts. Another example is Campbell et al who have studied using parametric computer-aided design (CAD) approaches for engaging customers and using AM to manufacture their customized parts [11]. However, not all of these research groups provide specifics about their proposed methods; rather many just advocate for more research.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to provide a comprehensive overview of rapid prototyping and the realization of equipment using AM. Campbell et al [4] shown that, in recent years, advances in AM have enabled the development of more representative prototypes. This entails that fully functional prototypes can be produced that are very close to the product, in terms of both material properties and visual appearance.…”
Section: Introductionmentioning
confidence: 99%